Use of an Errorless Learning Approach in a Person With Concomitant Traumatic Spinal Cord Injury and Brain Injury: A Case Report. Issue 2 (April 2018) - Hartmann, Annie; Kegelmeyer, Deb; Kloos, Anne
Abstract : N/A: Individuals with concomitant spinal cord injury and traumatic brain injury have cognitive deficits that may limit the ability to learn novel motor tasks necessary for functional independence. Errorless learning has been shown to improve cognitive task performance in persons with brain injury but little is known about its usefulness for improving novel motor task learning. Case Description: A 44-year-old man with traumatic spinal cord and brain injuries from a motor vehicle accident was admitted to an inpatient rehabilitation hospital. His spinal cord injury was classified as T4 American Spinal Injury Association Impairment Scale (AIS) A, and his cognitive status was level IV on the Ranchos Los Amigos Scale. Initially, the patient required maximal assistance from 2 clinicians to complete a slide board transfer, propelled his wheelchair 25 ft with minimal assistance, and scored 9/56 on the Function in Sitting Test. Intervention: The therapist applied traditional motor-learning approaches during the first 37 days of the patient's inpatient rehabilitation facility stay without meaningful gains in functional mobility. A subsequent change to errorless learning was made for the following 32 days until discharge. Outcomes: After use of errorless learning, the patient performed novel mobility-related tasks of slide board transfers with minimal assistance and wheelchair propulsion without physical assistance up to 150 ft; the Function in Sitting Test score improved to 18/56. His sensorimotor system progressed to an AIS classification of AIS B, while his cognition emerged to a level V on the Ranchos Los Amigos Scale. Discussion: Errorless learning may have facilitated acquisition of novel transfer and mobility skills in this individual with dual diagnoses. This approach may have value for patients with neurologic conditions who have both motor and cognitive impairment. Video Abstract available for more insights from the authors (see Video, Supplemental Digital Content 1, http://links.lww.com/JNPT/A201 ). Abstract : Supplemental Digital Content is Available in the Text.